1999
DOI: 10.1084/jem.190.7.995
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Interleukin 10 in the Function of Regulatory T Cells That Inhibit Intestinal Inflammation

Abstract: A T helper cell type 1–mediated colitis develops in severe combined immunodeficient mice after transfer of CD45RBhigh CD4+ T cells and can be prevented by cotransfer of the CD45RBlow subset. The immune-suppressive activities of the CD45RBlow T cell population can be reversed in vivo by administration of an anti-transforming growth factor β antibody. Here we show that interleukin (IL)-10 is an essential mediator of the regulatory functions of the CD45RBlow population. This population isolated from IL-10–deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
1,033
6
13

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,403 publications
(1,089 citation statements)
references
References 31 publications
37
1,033
6
13
Order By: Relevance
“…These cytokines are important in cell mediated suppression and crucial in the generation of regulatory FoxP3+ T cells (Powrie et al, 1996;Asseman et al, 1999;Maloy and Powrie, 2001;Green et al, 2003). The impact of IL-10 and TGF-β on the suppressive function mediated by the SAg fusion constructs in the EAE model was investigated by neutralization of cytokines.…”
Section: Tolerogenic Capacity Of Sag Constructs Depends On Il-10 and mentioning
confidence: 99%
“…These cytokines are important in cell mediated suppression and crucial in the generation of regulatory FoxP3+ T cells (Powrie et al, 1996;Asseman et al, 1999;Maloy and Powrie, 2001;Green et al, 2003). The impact of IL-10 and TGF-β on the suppressive function mediated by the SAg fusion constructs in the EAE model was investigated by neutralization of cytokines.…”
Section: Tolerogenic Capacity Of Sag Constructs Depends On Il-10 and mentioning
confidence: 99%
“…Also, Treg isolated from secondary lymphoid organs of normal mice do not produce IL-10 or TGF-b upon re-stimulation. In contrast, there is evidence that IL-10 and TGF-b may be relevant mediators of suppression in vivo [6][7][8][9][10][11] and Treg isolated from sites of active immune reactions are able to produce high amounts of IL-10 upon re-stimulation [7,11,12]. Recent data indicate that IL-2 is critical for the activation of Treg effector function, such as production of IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the lack of involvement of cytokines in CD25 + -mediated suppression in vitro, IL-10, IL-4, and TGF-β have been implicated as mediating suppression of some 22 23 24, but not all (25, and unpublished observations), autoimmune diseases by Tr cells. While IL-10 is produced by the Tr cells 24, it has not yet been shown that IL-4 or TGF-β are actually produced by CD25 + regulatory cells in vivo.…”
Section: Mechanism Of Suppressionmentioning
confidence: 83%
“…While IL-10 is produced by the Tr cells 24, it has not yet been shown that IL-4 or TGF-β are actually produced by CD25 + regulatory cells in vivo. Thus, it is difficult to conclude if these cytokines are responsible for the suppressive effects of the Tr cells or if they play a role in the differentiation of the Tr cells.…”
Section: Mechanism Of Suppressionmentioning
confidence: 99%